Potential type carbon dioxide sensor based on porous spherical ZnCo2O4-ZnO sensitive electrode
By combining a porous spherical ZnCo2O4-ZnO sensitive electrode with a yttrium-doped zirconium oxide electrolyte substrate, the problems of insufficient mechanical stability and conductivity of the sensor are solved, realizing a high-precision, self-cleaning carbon dioxide sensor suitable for industrial waste gas, indoor air quality detection, and medical respiratory analysis.
Patent Information
- Application Number
- CN202511551226.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2026-01-27
AI Technical Summary
Existing carbon dioxide sensors have weak mechanical stability during long-term cycling, and the conductivity and mechanical stability of sulfide materials are insufficient, making it difficult to meet the requirements for high-precision and high-temperature carbon dioxide monitoring.
A porous spherical ZnCo2O4-ZnO sensitive electrode was used, combined with a yttrium-doped zirconium oxide solid electrolyte substrate and a platinum reference electrode. Porous carbon nanofibers were prepared by electrospinning and melt diffusion methods to form a stable electrochemical sensor structure.
It significantly improves the sensor's surface area and gas diffusion performance, enhances its responsiveness and selectivity to carbon dioxide, and features a self-cleaning function, making it suitable for high-precision monitoring in complex environments.
Smart Images

Figure CN121410073A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of gas sensing technology, specifically to a potential-type carbon dioxide sensor based on a porous spherical ZnCo2O4-ZnO sensitive electrode. Background Technology
[0002] Greenhouse gases are the main optically active components of the atmosphere that determine global climate. Carbon dioxide, as one of the most significant greenhouse gases, accounts for over 60% of the total variation in radiative forcing caused by long-lived greenhouse gases. Since the Industrial Revolution, with the large-scale combustion of fossil fuels and changes in land use patterns, anthropogenic emissions of carbon dioxide have increased significantly. According to statistics from the U.S. National Oceanic and Atmospheric Administration (NOAA), the global average atmospheric carbon dioxide concentration in March 2023 was 421 ppm, far exceeding the pre-Industrial Revolution level of 278 ppm, setting a new historical record.
[0003] However, over the past 10 years, the average annual absolute increase in carbon dioxide mole fraction has been only 2.38 ppm. Continuous and high-precision monitoring of atmospheric CO2 concentration provides data support for global climate models and is a fundamental and crucial pillar for understanding and controlling global climate change. An increase in the volume fraction of carbon dioxide in the atmosphere can lead to rising temperatures and ocean acidification, and may also directly harm human health. To gain a deeper understanding of the relationship between carbon dioxide and people's production and lives, in-situ detection of carbon dioxide levels in the environment is essential.
[0004] Over the past few decades, scientists have conducted research on CO2 sensors from optical and electrochemical perspectives. Potential-based CO2 sensors using semiconductor metal oxides have become a recent research hotspot due to their simple structure and wide applicability. Compared to oxides, sulfides such as CoS2, NiS4, CuS, MoS2, and ZnS possess more complex valence states, which are beneficial for ion intercalation and redox reactions in the electrolyte. Among them, CoS2 exhibits advantages such as high capacity, low internal resistance, high rate performance, and good capacity retention, making it a highly promising material. However, sulfides exhibit weak mechanical stability during long-term cycling, typically requiring combination with carbon materials to further improve their conductivity and mechanical stability. Summary of the Invention
[0005] The main objective of this invention is to overcome the deficiencies in the aforementioned background technology and provide a low-carbon emission automotive intake particulate matter online monitoring sensor and its components with self-cleaning function, which has advantages such as real-time monitoring, self-cleaning, stable operation at high temperatures, and strong anti-pollution capability.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A potential-type carbon dioxide sensor based on a porous spherical ZnCo2O4-ZnO sensitive electrode includes: a solid electrolyte substrate made of yttrium-doped zirconium oxide; a reference electrode disposed on one side surface of the solid electrolyte substrate and made of platinum; a sensitive electrode disposed on the other side surface of the solid electrolyte substrate and made of porous spherical ZnCo2O4-ZnO; a signal acquisition component including two platinum leads connected to the reference electrode and the sensitive electrode respectively; and a fixing assembly that fixes the platinum leads to the reference electrode and the sensitive electrode respectively using silver paste and forms a connection through high-temperature sintering.
[0007] Optionally, the solid electrolyte substrate is a square sheet with a thickness of 0.5 mm and a side length of 10 mm.
[0008] Optionally, the reference electrode is formed by screen printing technology, with a coverage area of 5 mm × 5 mm and a thickness of 10 micrometers.
[0009] Optionally, the sensitive electrode is formed by screen printing technology, with a coverage area of 5 mm × 5 mm and a thickness of 22 micrometers.
[0010] Optionally, the fabrication process of the sensitive electrode includes the following steps: Take 1.5 grams of cobalt nitrate hexahydrate, zinc nitrate hexahydrate and ammonium carbonate in a mass ratio of 1:2:2, dissolve them in 50 ml of deionized water, and sonicate for 15 minutes. The solution was then poured into a stainless steel hydrothermal reactor lined with polytetrafluoroethylene and kept at 180 degrees Celsius for 10 hours to obtain the ZnCo2O4 precursor. The precursor was cooled to room temperature and then subjected to vacuum filtration, deionized water washing and drying. It was then placed in air and annealed at 400 degrees Celsius for 2 hours to obtain ZnCo2O4 powder. The particle size was refined by grinding the ZnCo2O4 nanoparticles at 400 rpm for 3 hours using a planetary ball mill; the ZnCo2O4 nanoparticles were mixed with polyacrylonitrile powder in a certain proportion and dissolved in dimethylformamide solution, and stirred at 60 degrees Celsius for 48 hours to form a spinning solution with a mass fraction of 8% and uniformly dispersed ZnCo2O4 nanoparticles. The spinning solution was loaded into a syringe, the distance between the needle and the aluminum foil receiver was set to 15 cm, and a voltage of 16 kV was applied for electrospinning. Then the spun precursor was placed in a tube furnace and pre-oxidized at 280 degrees Celsius for 2 hours, and then heated to the target temperature and held for 6 hours in a xenon atmosphere to finally obtain ZnCo2O4 / PAN porous carbon nanofibers. The ZnCo2O4 / PAN porous carbon nanofibers were mixed with sulfur by melt diffusion method, ground for 10 minutes, and then transferred to a polytetrafluoroethylene liner. The mixture was then kept at 155 degrees Celsius for 2 hours under argon protection to obtain the ZnCo2O4 / PAN / S composite cathode material.
[0011] Optionally, the preparation process of the reference electrode includes the following steps: A platinum reference electrode with uniform thickness is formed by screen printing platinum paste on one side surface of the solid electrolyte substrate. The solid electrolyte substrate printed with the platinum reference electrode was placed in an oven at 150 degrees Celsius and baked for 45 minutes, then sintered at 1000 degrees Celsius for 2 hours, and finally cooled naturally to room temperature.
[0012] Optionally, the assembly process of the sensitive electrode includes the following steps: The prepared ZnCo2O4 powder was mixed with an organic binder to form a uniform electrode slurry. The electrode paste is coated onto the other side surface of the solid electrolyte substrate using screen printing technology; A small amount of silver paste was dipped into one end of a platinum wire with a diameter of 0.2 mm and fixed onto the surface of the sensitive electrode, and then dried at 100 degrees Celsius for 30 minutes. The assembled sensor was heated to 1100 degrees Celsius at a heating rate of 2 degrees Celsius per minute for sintering, and then allowed to cool naturally to room temperature.
[0013] Optionally, the organic binder consists of 70 wt.% terpineol, 29 wt.% ethyl cellulose and 1 wt.% Span 80.
[0014] Optionally, the fixing assembly fixes the platinum leads to the reference electrode and the sensitive electrode with silver paste, and bakes them in an 80°C drying oven for 45 minutes. Then, the solid electrolyte substrate is heated to 150°C at a heating rate of 5°C per minute for densification sintering, followed by natural cooling.
[0015] Optionally, the platinum lead in the signal acquisition component has a diameter of 0.2 mm.
[0016] The beneficial effects of this invention are as follows: The design and fabrication of porous spherical ZnCo2O4-ZnO materials significantly improved the surface area and gas diffusion performance of the sensitive electrode, thereby enhancing the sensor's response to carbon dioxide gas. X-ray diffraction analysis showed that the ZnCo2O4 material has high crystallinity and can effectively participate in electrochemical reactions. Scanning electron microscopy revealed that the sensitive electrode exhibits a loose porous structure composed of short rod-shaped particles, which is conducive to the adsorption and diffusion of gas molecules. Furthermore, the solid electrolyte is yttrium-doped zirconium oxide, which possesses excellent high-temperature resistance and ionic conductivity, providing a stable electrochemical environment for the sensor. Test results show that the sensor exhibits rapid response and recovery characteristics to different concentrations of carbon dioxide gas at an operating temperature of 450℃, producing response values of -75mV and -30mV for 80ppm and 40ppm carbon dioxide, respectively, demonstrating good low-concentration detection capability. Simultaneously, the sensor's selectivity for carbon dioxide is significantly better than that for other gases, with low cross-sensitivity, making it suitable for high-precision monitoring requirements in complex environments. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the potential-type gas sensor based on YSZ solid electrolyte and ZnCo2O4 sensitive electrode as described in this invention. Figure 2 The XRD patterns of ZnCo2O4 powder and YSZ electrolyte GDC in this invention are shown (the horizontal axis represents angle and the vertical axis represents intensity). Figure 3 This is a planar SEM image of the ZnCo2O4 sensitive electrode material in this invention; Figure 4 The response recovery curves of the potential sensor fabricated using YSZ substrate and ZnCo2O4 sensitive electrode material in this invention to different concentrations of carbon dioxide are shown. Figure 5 The above is the carbon dioxide sensitivity curve of the potential sensor fabricated using YSZ substrate and ZnCo2O4 sensitive electrode material in this invention. Figure 6 This is a schematic diagram illustrating the selectivity of a potential-type sensor for carbon dioxide and its cross-sensitivity to other gases, fabricated using a YSZ substrate and ZnCo2O4 sensitive electrode material in this invention. Detailed Implementation
[0018] The technical solutions of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. The components of this application described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of this application provided in the accompanying drawings is not intended to limit the scope of the claimed application, but merely represents selected embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application. It should be noted that similar reference numerals and letters in the following drawings indicate similar items; therefore, once an item is defined in one drawing, it does not need to be further defined and explained in subsequent drawings. Furthermore, in the description of this application, the terms "first," "second," etc., are used only to distinguish descriptions and should not be construed as indicating or implying relative importance. Example
[0019] This application proposes a potential-type carbon dioxide sensor based on a porous spherical ZnCo2O4-ZnO sensitive electrode, comprising a solid electrolyte substrate, a reference electrode, a sensitive electrode, platinum leads, and silver paste fixing points.
[0020] The solid electrolyte substrate, serving as the core supporting structure of the sensor, is made of yttrium-doped zirconium oxide (YSZ), exhibiting excellent ionic conductivity and mechanical stability. The solid electrolyte substrate is a square sheet, 0.5 mm thick and 10 mm on each side. The reference electrode, made of platinum, is disposed on one surface of the solid electrolyte substrate.
[0021] The sensitive electrode, composed of porous spherical ZnCo2O4-ZnO material, is disposed on the other side of the solid electrolyte substrate. Two platinum leads are connected to the reference electrode and the sensitive electrode respectively via silver paste fixing points, used to transmit electrochemical signals to external testing equipment. The fixing assembly securely fixes the platinum leads to the electrodes with silver paste and forms a stable connection through high-temperature sintering.
[0022] The preparation process of the sensitive electrode is as follows: First, weigh out 1.5 grams of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), zinc nitrate hexahydrate (Zn(NO3)2·6H2O), and ammonium carbonate ((NH4)2CO3) in a mass ratio of 1:2:2, and dissolve them in 50 ml of deionized water. Sonicate the solution for 15 minutes to ensure thorough mixing.
[0023] The solution was then poured into a polytetrafluoroethylene-lined stainless steel hydrothermal reactor and kept at 180°C for 10 hours to obtain the ZnCo2O4 precursor. After the reaction was complete, the precursor was cooled to room temperature and subjected to vacuum filtration, washing with deionized water, and drying.
[0024] The dried precursor was then annealed in air at 400°C for 2 hours to obtain ZnCo2O4 powder. The powder was further refined by grinding in a planetary ball mill at 400 rpm for 3 hours.
[0025] Subsequently, ZnCo2O4 nanoparticles were mixed with polyacrylonitrile (PAN) powder in a certain proportion and dissolved in dimethylformamide (DMF) solution. The mixture was stirred at 60°C for 48 hours to form a spinning solution with a mass fraction of 8% and uniformly dispersed ZnCo2O4 nanoparticles.
[0026] The spinning solution was loaded into a syringe, and the distance between the needle and the aluminum foil receiver was set to 15 cm. Electrospinning was performed by applying a voltage of 16 kV. The spinning solution was continuously stirred during the spinning process to prevent particle agglomeration. The spun precursor was then placed in a tube furnace and pre-oxidized at 280°C for 2 hours, followed by heating to the target temperature and holding for 6 hours in a xenon atmosphere, ultimately yielding ZnCo2O4 / PAN porous carbon nanofibers.
[0027] Finally, the ZnCo2O4 / PAN porous carbon nanofibers were mixed with sulfur (S) by melt diffusion method, ground for 10 minutes, and then transferred to a polytetrafluoroethylene liner. The mixture was then kept at 155℃ for 2 hours under argon protection to obtain the ZnCo2O4 / PAN / S composite cathode material.
[0028] The preparation process of the reference electrode is as follows: Platinum paste is screen-printed onto one side of a solid electrolyte substrate to form a platinum reference electrode with uniform thickness. The thickness of the platinum paste is controlled at approximately 10 micrometers, covering an area of 5 mm × 5 mm. The solid electrolyte substrate with the printed platinum reference electrode is placed in an oven at 150°C and baked for 45 minutes, followed by sintering at 1000°C for 2 hours, and finally naturally cooled to room temperature. During the sintering process, the organic components in the platinum paste are completely decomposed, leaving a pure platinum layer, ensuring that the reference electrode possesses good conductivity and stability.
[0029] The assembly process of the sensitive electrode is as follows: The prepared ZnCo2O4 powder is mixed with an organic binder to form a uniform electrode slurry. The organic binder consists of 70 wt.% terpineol, 29 wt.% ethyl cellulose, and 1 wt.% Span 80, and its function is to improve the coating performance and adhesion of the slurry.
[0030] Electrode paste was coated onto the other side of a solid electrolyte substrate using screen printing technology to form a sensitive electrode with dimensions of 5 mm × 5 mm and a thickness of 22 micrometers. After coating, a small amount of silver paste was dipped into one end of a 0.2 mm diameter platinum wire and fixed onto the surface of the sensitive electrode, which was then dried at 100°C for 30 minutes.
[0031] The assembled sensor was heated to 1100℃ at a heating rate of 2℃ / min for sintering, and then naturally cooled to room temperature. During the sintering process, the organic binder completely decomposed, leaving porous spherical ZnCo2O4-ZnO material.
[0032] Figure 3 The SEM microstructure of the ZnCo2O4 sensitive electrode after sintering at 900~1300℃ is shown. It can be seen that the sensitive electrode is composed of short rod-shaped particles and exhibits a loose and porous structure, which is conducive to the diffusion and reaction of gas inside the electrode.
[0033] The overall molding process of the sensor is as follows: a small amount of silver paste is applied to the reference electrode and the sensitive electrode with a platinum wire, and then the wire is placed in a drying oven and baked at 50℃~100℃ for 30~60 minutes.
[0034] The solid electrolyte substrate is heated to 100℃~200℃ at a heating rate of 4~6℃ / min for densification sintering, and then naturally cooled to ensure that the platinum wire is tightly bonded to the solid electrolyte substrate.
[0035] After sintering, a potential-type carbon dioxide sensor based on a ZnCo2O4 sensitive electrode and a YSZ solid electrolyte was obtained. The overall structure of the sensor is as follows. Figure 1 As shown, the solid electrolyte substrate is located in the center, the reference electrode and the sensitive electrode are located on both sides, and the platinum leads are connected to the electrodes through silver paste fixing points.
[0036] The sensor works as follows: When the sensor is exposed to an environment containing carbon dioxide, carbon dioxide molecules diffuse into the porous structure of the sensitive electrode. Because the sensitive electrode is made of porous spherical ZnCo2O4-ZnO material, it has a large surface area and excellent gas diffusion performance, enabling it to effectively adsorb carbon dioxide molecules.
[0037] Carbon dioxide molecules undergo an electrochemical reaction on the surface of the sensitive electrode, causing a change in the electrode potential. The reference electrode provides a stable electrochemical reference signal, which is transmitted to external testing equipment via platinum leads. The external equipment then calculates the carbon dioxide concentration based on the potential change.
[0038] Figure 2The image shows the XRD (X-ray diffraction) pattern of the prepared ZnCo2O4 sensitive electrode material. The sharp diffraction peaks indicate the high crystallinity of ZnCo2O4. Comparison shows that the diffraction peaks of the synthesized electrode material are in high agreement with the standard card, indicating that the ZnCo2O4 sensitive electrode material was successfully synthesized in this invention.
[0039] Figure 3 The SEM microstructure of the ZnCo2O4 sensitive electrode after sintering at 900~1300℃ is shown. It can be seen that the sensitive electrode is composed of short rod-shaped particles and exhibits a loose and porous structure, which is conducive to the diffusion and reaction of gas inside the electrode.
[0040] The prepared carbon dioxide sensor was placed in a tubular furnace quartz tube, and the Pt leads of the sensitive and reference electrodes were connected to an electrochemical workstation. The flow rate and composition of the gas being measured were controlled by a mass flow meter, with a total gas flow rate of 0.5 L / min. The base gas composition included 10 vol.% O2 and 90 vol.% N2, while the sample gas composition was 2-80 ppm CO2, 10 vol.% O2, and the remainder N2. The test temperature was 450℃. The sensor signals acquired by the electrochemical workstation were displayed on a computer.
[0041] The specific testing process is as follows: (1) After the sensor is heated to the working temperature, the base gas is introduced into the quartz tube. When the sensor signal (potential difference between the sensitive and reference electrodes) reaches a stable state, the signal value Vbasegas of the sensor in the base gas is obtained.
[0042] (2) The gas to be measured with different CO2 concentrations is passed into the quartz tube, and the signal value VCO2 of the sensor in CO2 is obtained when the signal is stable.
[0043] (3) The base gas is reintroduced into the quartz tube. When the sensor signal recovers to the base gas signal value, the sensor completes one response and recovery process. The signal difference ΔV (ΔV = VCO2 - Vbasegas) between the sensor in CO2 and the base gas is the sensor's response value for that concentration of CO2.
[0044] Figure 4 The response characteristics of a sensor based on a ZnCo2O4 sensitive electrode, sintered at 900~1300℃, to different concentrations of CO2 are shown in the graphs. The horizontal axis represents time, and the vertical axis represents the response value. The operating temperature is 450℃. It can be seen that at the operating temperature of 450℃, the sensor exhibits a relatively fast response and recovery process to the analyte gas with different CO2 concentrations. It shows response values of -75mV and -30mV for 80ppm and 40ppm CO2, respectively, indicating that the sensor has good detection capability for low-concentration CO2.
[0045] Figure 5 The sensor based on a ZnCo2O4 sensitive electrode sintered at 900~1300℃ shows the response values to different CO2 concentrations, with the x-axis representing CO2 concentration and the y-axis representing the response value. The operating temperature is 450℃. It can be seen that there is a good linear relationship between the response value and the logarithm of the gas concentration. According to the mixing potential mechanism, the slope of this linear relationship line represents the sensor's sensitivity. The calculated CO2 sensitivity of the sensor is 22.85 mV / decade, exhibiting high CO2 sensitivity.
[0046] Figure 6 The graph shows the response values of a sensor using ZnCo2O4 as the sensing electrode to different gases at a concentration of 10 ppm. The horizontal axis represents the sensor response value, and the vertical axis represents the composition of the gas being measured. All concentrations are 10 ppm, and the operating temperature is 500℃. The sensor exhibits the highest response value to CO2, reaching -20 mV, while the response values to other gases are all less than -2 mV, indicating that the sensor has excellent CO2 selectivity and low cross-sensitivity to other gases.
[0047] The sensor of this invention is applicable to various practical scenarios, such as industrial waste gas monitoring, indoor air quality detection, and medical respiratory analysis. In industrial waste gas monitoring, the sensor can be installed in chimneys or exhaust ducts to monitor carbon dioxide concentration in real time, ensuring emissions meet environmental standards. In indoor air quality detection, the sensor can be integrated into air purifiers or smart home systems to monitor indoor carbon dioxide levels and automatically adjust ventilation equipment.
[0048] In medical respiratory analysis, sensors can be used to detect the concentration of carbon dioxide in a patient's exhaled breath, aiding in the diagnosis of respiratory diseases. This invention significantly improves the sensor's sensitivity, selectivity, and response speed for carbon dioxide gas detection by optimizing the material structure and fabrication method of the sensitive electrode, while reducing cross-sensitivity, thus meeting the requirements for high-precision monitoring.
[0049] To enable those skilled in the art to fully understand and implement this invention, the specific implementation principle of this invention is further explained below with reference to a specific application scenario. In an industrial waste gas monitoring scenario, the sensor is first installed at the detection port of the exhaust pipe.
[0050] The solid electrolyte substrate, serving as the core support structure of the sensor, is made of yttrium-doped zirconium oxide (YSZ) material. It is 0.5 mm thick and 10 mm on each side, capable of withstanding high temperatures and providing stable ionic conductivity. The reference electrode, made of platinum and covering an area of 5 mm × 5 mm, is located on one side of the solid electrolyte substrate and provides a stable electrochemical reference signal. The sensitive electrode, also 5 mm × 5 mm and 22 μm thick, is located on the other side of the solid electrolyte substrate. Two platinum leads are connected to the reference and sensitive electrodes via silver paste fixing points and then sintered at high temperature to form a robust connection, ensuring stable signal transmission.
[0051] When the sensor is exposed to industrial waste gas containing carbon dioxide, carbon dioxide molecules diffuse into the porous structure of the sensitive electrode. Because the sensitive electrode is composed of a loose, porous structure of short rod-shaped particles, it has a large surface area and excellent gas diffusion properties, effectively adsorbing carbon dioxide molecules. The carbon dioxide molecules undergo an electrochemical reaction on the surface of the sensitive electrode, causing a change in the electrode potential. The reference electrode provides a stable electrochemical reference signal, which is transmitted to external testing equipment via platinum leads. The external equipment calculates the carbon dioxide concentration based on the potential change.
[0052] During this process, the high crystallinity of ZnCo2O4 material ensures its effective participation in the electrochemical reaction, thereby improving the sensor's sensitivity. In actual operation, the sensor's operating temperature is set at 450℃ to optimize its response characteristics. At this temperature, the sensor exhibits rapid response and recovery characteristics to different concentrations of carbon dioxide gas. For example, when the carbon dioxide concentration is 80 ppm, the sensor produces a response value of -75 mV; when the concentration decreases to 40 ppm, the response value decreases accordingly to -30 mV. This good linear relationship enables the sensor to accurately detect low concentrations of carbon dioxide gas, meeting the needs of industrial waste gas monitoring.
[0053] Furthermore, the sensor's selectivity was further validated in complex gas environments. The sensor responded significantly better to carbon dioxide than to other gases, exhibiting low cross-sensitivity. This characteristic is attributed to the porous spherical structure of the sensitive electrode and the optimized design of the ZnCo2O4-ZnO material, enabling it to accurately identify carbon dioxide even in the presence of multiple gases. In indoor air quality monitoring scenarios, the sensor can be integrated into air purifiers or smart home systems.
[0054] The sensor monitors indoor carbon dioxide levels in real time, transmits the data to the control system, and automatically adjusts the operation of the ventilation equipment. This process relies on the sensor's rapid response characteristics and low-concentration detection capability to ensure that indoor air quality is always maintained within a healthy range.
[0055] In medical respiratory analysis, sensors are used to detect the carbon dioxide concentration in a patient's exhaled breath. The sensors' high sensitivity and selectivity enable them to detect minute changes in carbon dioxide levels, thus aiding in the diagnosis of respiratory diseases. For example, when the carbon dioxide concentration in a patient's exhaled breath is abnormally high, the sensor can quickly detect this change and generate a corresponding data report via external devices, providing doctors with diagnostic information.
[0056] In summary, by optimizing the material structure and preparation method of the sensitive electrode, this invention significantly improves the sensor's detection sensitivity, selectivity, and response speed for carbon dioxide gas, while reducing cross-sensitivity, thus meeting the high-precision monitoring requirements of various practical application scenarios.
[0057] The above description is merely an embodiment of this application and is not intended to limit the scope of protection of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A potential-type carbon dioxide sensor based on a porous spherical ZnCo2O4-ZnO sensitive electrode, characterized in that, include: A solid electrolyte substrate, wherein the solid electrolyte substrate is made of yttrium-doped zirconium oxide material; A reference electrode, disposed on one side surface of the solid electrolyte substrate, is made of platinum material; a sensitive electrode, disposed on the other side surface of the solid electrolyte substrate, is made of porous spherical ZnCo2O4-ZnO material; a signal acquisition component includes two platinum leads, which are respectively connected to the reference electrode and the sensitive electrode; and a fixing assembly, which fixes the platinum leads to the reference electrode and the sensitive electrode respectively with silver paste and forms a connection by high-temperature sintering.
2. The potential-type carbon dioxide sensor according to claim 1, characterized in that, The solid electrolyte substrate is a square sheet with a thickness of 0.5 mm and a side length of 10 mm.
3. The potential-type carbon dioxide sensor according to claim 1, characterized in that, The reference electrode is formed by screen printing technology, with a coverage area of 5 mm × 5 mm and a thickness of 10 micrometers.
4. The potential-type carbon dioxide sensor according to claim 1, characterized in that, The sensitive electrode is formed by screen printing technology, with a coverage area of 5 mm × 5 mm and a thickness of 22 micrometers.
5. The potential-type carbon dioxide sensor according to claim 1, characterized in that, The preparation process of the sensitive electrode includes the following steps: Take 1.5 grams of cobalt nitrate hexahydrate, zinc nitrate hexahydrate and ammonium carbonate in a mass ratio of 1:2:2, dissolve them in 50 ml of deionized water, and sonicate for 15 minutes. The solution was then poured into a stainless steel hydrothermal reactor lined with polytetrafluoroethylene and kept at 180 degrees Celsius for 10 hours to obtain the ZnCo2O4 precursor. The precursor was cooled to room temperature and then subjected to vacuum filtration, deionized water washing and drying. It was then placed in air and annealed at 400 degrees Celsius for 2 hours to obtain ZnCo2O4 powder. The particle size was refined by grinding the ZnCo2O4 nanoparticles at 400 rpm for 3 hours using a planetary ball mill; the ZnCo2O4 nanoparticles were mixed with polyacrylonitrile powder in a certain proportion and dissolved in dimethylformamide solution, and stirred at 60 degrees Celsius for 48 hours to form a spinning solution with a mass fraction of 8% and uniformly dispersed ZnCo2O4 nanoparticles. The spinning solution was loaded into a syringe, the distance between the needle and the aluminum foil receiver was set to 15 cm, and a voltage of 16 kV was applied for electrospinning. Then the spun precursor was placed in a tube furnace and pre-oxidized at 280 degrees Celsius for 2 hours, and then heated to the target temperature and held for 6 hours in a xenon atmosphere to finally obtain ZnCo2O4 / PAN porous carbon nanofibers. The ZnCo2O4 / PAN porous carbon nanofibers were mixed with sulfur by melt diffusion method, ground for 10 minutes, and then transferred to a polytetrafluoroethylene liner. The mixture was then kept at 155 degrees Celsius for 2 hours under argon protection to obtain the ZnCo2O4 / PAN / S composite cathode material.
6. The potential-type carbon dioxide sensor according to claim 1, characterized in that, The preparation process of the reference electrode includes the following steps: A platinum reference electrode with uniform thickness is formed by screen printing platinum paste on one side surface of the solid electrolyte substrate. The solid electrolyte substrate printed with the platinum reference electrode was placed in an oven at 150 degrees Celsius and baked for 45 minutes, then sintered at 1000 degrees Celsius for 2 hours, and finally cooled naturally to room temperature.
7. The potential-type carbon dioxide sensor according to claim 1, characterized in that, The assembly process of the sensitive electrode includes the following steps: The prepared ZnCo2O4 powder was mixed with an organic binder to form a uniform electrode slurry. The electrode paste is coated onto the other side surface of the solid electrolyte substrate using screen printing technology; A small amount of silver paste was dipped into one end of a platinum wire with a diameter of 0.2 mm and fixed onto the surface of the sensitive electrode, and then dried at 100 degrees Celsius for 30 minutes. The assembled sensor was heated to 1100 degrees Celsius at a heating rate of 2 degrees Celsius per minute for sintering, and then allowed to cool naturally to room temperature.
8. The potential-type carbon dioxide sensor according to claim 7, characterized in that, The organic binder consists of 70 wt.% terpineol, 29 wt.% ethyl cellulose and 1 wt.% Span 80.
9. The potential-type carbon dioxide sensor according to claim 1, characterized in that, The fixing assembly fixes the platinum leads to the reference electrode and the sensitive electrode with silver paste and bakes them in an 80°C drying oven for 45 minutes. Then, the solid electrolyte substrate is heated to 150°C at a heating rate of 5°C per minute for densification sintering and then naturally cooled.
10. The potential-type carbon dioxide sensor according to claim 1, characterized in that, The platinum lead in the signal acquisition component has a diameter of 0.2 mm.
